Field notes contributed by Thomas J. Staudt, winter 1982-1983 - Staudt, Thomas J.et al (1982)
Winter report of birds and locations contributed by Thomas J. Staudt. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of 1982-1983. Epson - sheet feed